High thermoelectric performance in GeTe with compositional insensitivity - Dong, Jinfeng (2022)
Thermoelectric materials have obtained worldwide attention as they are attractive for waste heat recovery and solid-state cooling. However, their performance is usually sensitive to material compositions, which is less favorable for industrial applications. In this work, we developed composition-insensitive GeTe-based compounds ((100-x-y)%GeTe-x%CuBiSe2-y%PbTe, CBSx-Pby) with high ZTmax as well as ZTave values. The compositional insensitivity can be associated with the persistently high quality factors across the range of compositions. This is largely due to the interplay between electrical and thermal transport caused by the synergy of CuBiSe2 and PbTe alloying. CuBiSe2 alloying can effectively tune the carrier concentrations, while PbTe alloying can significantly decrease the thermal conductivity at a minor sacrifice of electrical properties. The combined effects of CuBiSe2 and PbTe alloying lead to high carrier mobility of 60 cm2V−1s−1 and low thermal conductivities for CBSx-Pby samples simultaneously. Consequently, high ZTave values of 1.4–1.5 in the temperature range of 400 K and 773 K for broad compositions (CBS3-Pby, y = 2 – 8 and CBSx-Pb6, x = 2 – 5) are achieved. A single-leg module is also fabricated, which shows a high power density of 1.46 W/cm2 and an excellent efficiency of 13.4%. The high ZTave with compositional insensitivity and the outstanding module performance demonstrate the promising large-scale application of the developed GeTe-based compositions.